My soul looks back in wonder, how I got over: black women’s narratives on spirituality, sexuality, and informal learning - McClish, Keondria E. (Kansas State University, 2018)
The purpose of this qualitative study was to explore how two Black women, born 1946 to 1964, discuss their sexuality in relation to their understanding of spirituality and informal learning. Using the Black Feminine Narrative Inquiry framework informed by womanism, Black feminism, and narrative structures used by Black women novelists, this qualitative study analyzed the vulnerable, empowered, and spirit-driven narratives (VES Narratives) collected from the participants to explore their experiences with spirituality, sexuality, and informal learning. The data collection methods included wisdom whisper talks to elicit spirituality and sexuality timelines and glean information from the participants’ treasure chests.
Keywords: Black women; Spirituality; Sexuality; Informal Learning; Black Feminine Narrative Inquiry; Wisdom Whisper